Apolipoprotein B and oxLDL levels in plasma of patients with diabetes, cardiovascular disease, and COVID-19 - Tronko, M.D.; Cherviakova, S.A.; Pushkarev, V.V.; Belchina, Y.B.; Kovzun, O.I.; Pushkarev, V.M.; Sokolova, L.K. (Доповіді НАН України, 2021)
Elevated levels of low-density lipoprotein (LDL-X) cholesterol, apolipoprotein B (ApoB), and especially oxidized LDL in plasma are associated with an increased risk of cardiovascular disease (CVD). The aim of the study was to determine the levels of ApoB and oxLDL in the blood of patients with diabetes mellitus (DM), CVD and COVID-19. ApoB and oxLDL were determined using enzyme-linked immunosorbent assay kits (Elabscience, USA). The measurements were performed at an optical wavelength of 450 nm. It was found that ApoB and oxLDL levels in the blood of patients with diabetes and, especially, with COVID-19 are substantially higher than in the blood of healthy people. Blood levels of ApoB and oxLDL are higher in patients with both COVID-19 and diabetes or CVD as com pared to patients with COVID-19 without comorbidities. Thus, the levels of ApoB and oxidized LDL may be the promising markers of severe COVID-19.